Prognostic significance of the sum of the diameters of single foci in multifocal papillary thyroid cancer: the concept of new-old tumor burden. (October 2020) - Manso, Jacopo; Censi, Simona; Roberti, Amir; Iacobone, Maurizio; Barollo, Susi; Bertazza, Loris; Galuppini, Francesca; Vianello, Federica; Albinger, Nora; Scaroni, Carla; Pennelli, Gianmaria; Mian, Caterina
Aim: The prognostic value of multifocality (Mu) in papillary thyroid cancer (PTC) remains controversial. The present study aimed to investigate this issue and test the possible prognostic significance of the sum of the diameters of single foci (SDSF), the total number of foci (TNF), and primary tumor size (PTS) in multifocal PTC. Methods: We retrospectively analyzed a single-center consecutive series of 370 PTCs. For multifocal cases we analyzed bilaterality occurrence, SDSF, TNF, and PTS. Results: Mu was observed in 41.1% PTCs, and bilaterality in 30%. Mu was associated with an advanced T-category. In bilateral multifocal PTC, the PTS was larger, and microPTC was less frequent, while T-categories were higher. Mu and bilaterality per se had no impact on prognosis. At univariate analysis, PTS, SDSF, vascular invasion, lymph node metastases, distant metastases, T-categories, Initial Risk Stratification System score, second treatment and TERT promoter mutation correlated with persistence/recurrence or death in the multifocal PTC group. On multivariate Cox proportional hazards regression analyses, SDSF again independently predicted persistence/recurrence or death in multifocal PTCs. We found that a cut-off for SDSF less than 40 mm was able to identify multifocal PTC patients with a very low risk of persistence/recurrence (negative predictive value 96.9%). Disease-free survival was significantly shorter in patients with multifocal PTCs and SDSF ⩾40 mm. Conclusions: Mu and bilaterality per se were not prognostically significant. SDSF emerged as a new independent prognostic factor for persistence/recurrence of multifocal PTC. SDSF might better represent the tumor burden in multifocal PTC, with SDSF < 40 mm identifying multifocal PTC patients with a good prognosis.